Change Takes Time: Anxiety and Depression Following Brief Psychodynamic Counseling in University Students - Costanza Franchini; Gaetano Maria Sciabica; Silvia Andreassi; Mara Morelli; Antonio Chirumbolo; Anna Maria Speranza; Alexandro Fortunato (Healthcare, 2026)
Background/Objectives: University students are particularly vulnerable to anxiety and depression, yet longitudinal evidence on the effectiveness of brief psychodynamic university counseling remains limited. This study evaluated the effectiveness of a brief psychodynamic counseling intervention using a four-time-point repeated-measures design, examining changes in depressive and anxiety symptoms immediately after treatment and at a three-month follow-up. Methods: A total of 108 university students (Mage = 22.7, SDAge = 2.67; 61% female) participated in a psychodynamic intervention consisting of four weekly sessions and a follow-up session three months later. Depressive and anxiety symptoms were assessed at four time points: after the initial consultation (T0), before treatment (T1), after the intervention (T2), and after the three-month follow-up (T3), using the Beck Depression Inventory-II and the Beck Anxiety Inventory. Longitudinal changes were examined using linear mixed-effects models controlling for age and biological sex. Results: Depressive symptoms remained stable during the waiting period, significantly decreased following counseling, and these improvements were maintained at follow-up. Anxiety symptoms also remained stable during the waiting period and immediately after treatment, but significantly decreased at the three-month follow-up compared with all previous assessments. Biological sex significantly predicted anxiety symptoms, with male students reporting lower anxiety than female students, whereas age was not associated with either outcome. Conclusions: Brief psychodynamic university counseling was associated with sustained reductions in depressive symptoms and delayed improvements in anxiety symptoms. These findings support the effectiveness of brief psychodynamic counseling and highlight the importance of longitudinal follow-up assessments to capture the temporal dynamics of psychological change.